Comparative study on the violin method books for beginners / Noor Farisah Noordin, Juwairiyah Zakaria and Ahmad Munir Mahzair - Noordin, Noor Farisah; Zakaria, Juwairiyah; Mahzair, Ahmad Munir (College of Creative Arts, 2024)
Finding an appropriate violin introductory method for beginners can be challenging for teachers. A comparative study was conducted on three different books that are known as beginner technique books. The books are Shinichi Suzuki's Suzuki Violin School Volume 1 (1970), Auer's Maia Bang's Violin Method (1991), and C. Paul Herfurth's A Tune A Day (1991). The objectives of the study were 1) to identify the similarities and differences between each technique book, as well as 2) to investigate the advantages and disadvantages of each technique book. Reviewing and addressing the objectives was accomplished through the utilization of the qualitative content analysis, which is a comparison technique. The finding of this study has discovered that these three method books have a lot in common with one another in terms of core ideas, teaching patterns, procedures, and theories. Despite this, their approaches are the most dissimilar. Although, these three method books are appealing to a wide range of students, depending on their talents and levels of aptitude, because each book employs a different instructional approach and has different learning objectives. The strategies that were selected were able to accommodate a variety of students according to their capabilities and talents. With regards to the efficacy of these three technique books, it is suggested that additional research be carried out.